Optimalisasi Pemberdayaan Masyarakat Melalui Pelatihan Pengelolaan Air Bersih di Desa Bale Kecamatan Tanantovea Kabupaten Donggala - Mustafa, Mustafa; Mahyudin Syam, Dedi; Sapriana, Sapriana; S. Syukur, Djunaedil; S. Sunuh, Herlina; Udin, Udin (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service activity is motivated by the limited understanding among Bale Village residents of the importance of sanitation around clean water sources, which can increase the risk of environment-based infectious diseases. The main goal of this activity is to improve the community's knowledge and skills in managing clean water and maintaining sanitation facilities independently. The implementation method used is participatory face-to-face training, consisting of material presentation, field demonstrations, and interactive discussions, which are then evaluated using pre-test and post-test instruments. The results show strong community enthusiasm; of 18 participants, 13 fully participated in the evaluation. Analysis results indicate a significant achievement: 92.30% (12 people) increased their knowledge scores on the criteria for clean water and sources of pollution, while the remaining 7.70% maintained their previous knowledge. In conclusion, education- and demonstration-based training is effective in enhancing the community's cognitive capacity. This success is expected to encourage the formation of independent clean water management groups to maintain environmental sanitation quality in the area